The economics of moon mining. (May 2020) - Sommariva, Andrea; Gori, Leonella; Chizzolini, Barbara; Pianorsi, Mattia
Abstract: The 50th anniversary of the first human landing on the Moon has revived the interest of space agencies and private companies on the Earth only natural satellite. Mining the Moon has become the topics of interest to the entire space community. This paper will address the following questions: (i) is space resource utilization by solely private markets sustainable, and (ii) if not, what type of public-private partnership are important/appropriate to enable the development of a private-sector market. Highlights: A business model based on private-public partnership results in net present value maximization. A private business model points to negative NPV. Montecarlo simulations for private-public partnership indicate very low probabilities of negative NPVs. Hence, government-prospecting missions are needed prior to private exploration missions.